Ethnobotany, bioactive compounds and pharmacology of Syzygium guineense (Willd.) DC: A review - Dogara, Abdulrahaman Mahmoud; Bradosty, Sarwan W.; Al-Zahrani, Ateeq Ahmed; Hamad, Saber W.; Almalki, Hussain D. (Journal of ethnopharmacology, 2025)
Plants possess the ability to synthesize a diverse array of primary and secondary metabolites. Secondary metabolites are of great importance as a result of their status as natural substances that have the potential to provide therapeutic benefits for human health. Due to its many uses in traditional medicine, Syzygium guineense (Willd.) DC extracts have been the subject of numerous pharmacological studies. African traditional medicine uses it to treat a variety of ailments, including epilepsy, diarrhea, stomach pain, malaria, coughs, fractures, wounds, asthma, sore throats, intercostal pain, and as a tonic. No comprehensive reviews of S. guineense have been found, according to our literature search. Consider the great potential of S. guineense to serve as valuable sources of discovery of medicinal substances. Aim of the study: The study compiles ethnobotany, bioactive compounds, and pharmacology of Syzygium guineense. Research publications have been searched utilizing the following platforms: Elsevier, Springer, Google Scholar, Taylor & Francis, Pub med, and Scopus. Research the terms "Syzygium guineense," "chemical composition," "antioxidant," "antibacterial," "anti-diabetic," "anticancer" and any other relevant terms. Traditionally, S. guineense parts has been used to cure thirty different diseases including malaria, cough and diabetes among others. Contains 205 different compounds between the class of flavonoids, alkaloids, tannins, terpenoids and many more. From the pharmacological point of view, it has been reported to possess strong antibacterial, antimalarial, antihypertensive, anti-tuberculosis, anthelmintic, anti-venom, antiulcer, analgesic, anti-inflammatory, and anti-diabetic properties. No observable toxic effect was recorded. This review showcases the various biological activities together with its safety profile back up the traditional uses and point to the possible use of the S. guineense compound as a natural therapeutic tool. To confirm the results of preclinical studies, additional well-designed clinical trials are required to evaluate the safety and effectiveness of S. guineense in humans. [Display omitted] •The study collects and analysed data pertaining to the Bioactive compounds and biological impacts of Syzygium guineense from 1998 to April 2024.•A total of 205 compounds and variety pharmacological activities of S. guineense are summarized.•This review puts forward the problems and the corresponding suggestions for the research, development and utilization of S. guineense.•To the best of our knowledge this is the first comprehensive review on Syzygium guineense despite its popular medicinal importance, so we shed light on this plant.